A “3S+f” Nephrometry Score System to Predict the Clinical Outcomes of Laparoscopic Nephron-Sparing Surgery - Zhang, Shudong; Qin, Zijian; Bi, Hai; Tao, Liyuan; Zhang, Fan; Zhang, Hongxian; Wang, Wei; Wu, Jitao; Huang, Yi; Ma, Lulin (Frontiers in Oncology, 2022)
Background: When we treat renal cell carcinoma by laparoscopic nephron-sparing surgery, it is essential to use an evaluation system to predict clinical outcomes. Hitherto,there are more than a dozen nephrometry score systems. In this study, through assessing the correlations between nephrometry score systems and clinical outcomes, we aim to provide a novel nephrometry score system—“3S+f” score system to simplify the evaluation of technical complexity of partial nephrectomy. Methods: We retrospectively collected the data of 131 patients who underwent NSS which performed by the single surgeon (SDZ) during the period from January 2013 to July 2018 of Peking University Third Hospital. “3S+f” score system contains four parameters: “size, side, site and fat”, which all can be obtained from preoperative imaging data. We evaluated the correlations between “3S+f” score and clinical outcomes, and compared to R.E.N.A.L. score and PADUA score. Results: All the three nephrometry score systems were related to some clinical outcomes in univariate analyses. In multivariate regression models, “3S+f” score, R.E.N.A.L. score and PADUA score were significantly associated with operative time (p=0.016, p=0.035, p=0.001, corresponding) and warm ischemia time (all p=0.008, p<0.001, p<0.001, corresponding). “3S+f” was also significantly related to extubation time>5days (p=0.018). In ROC curves, AUC of “3S+f” score (0.717, 0.652, corresponding) was more than R.E.N.A.L (0.598, 0.554, corresponding) and PADUA (0.600, 0.542, corresponding) score in operative time>120minutes and extubation time>5days. Conclusion: A novel nephrometry score system—“3S+f” score system shows equivalent correlation and ability in predicting clinical outcomes when compared to R.E.N.A.L. score system and PADUA score system, which can describe renal tumors.